Manwal para sa mga Community-Based Rehabilitation (CBR) worker - Magallona, Ma. Lucia Mirasol (Sistemang Unibersidad ng Pilipinas at Kagawaran sa Agham at Teknolohiya, 1996)
This manual was produced based on the author's own experiences as a community-based rehabilitation (CBR) worker from the UP College of Allied Medical Professions. It aims to help CBR workers, especially volunteers, who cater to disabled persons. It tackles the rights of disabled persons; issues faced by them; ways to prevent, identify, and rehabilitate different disabilities; and common methods of therapy. Text is in Filipino.